A macroeconomics‐inspired interpretation of the terrestrial water cycle. (4th September 2019) - Ungvári, Gábor; Kis, András
Abstract: This article develops an approach that applies macroeconomic concepts to the interpretation of complex, water related natural processes. By translating and re‐interpreting these processes into a language that is more accessible to a broader audience otherwise unaccustomed to its terms will likely help sharpen our understanding of the terrestrial water cycle. For economists, we describe climate‐forming natural processes in a manner consistent with the fundamentals of the mainstream approach. For noneconomists, parallels from economically determined, relatively short‐term observations can be applied conceptually to identify dynamics which occur over much longer and therefore more elusive natural occurrences, in particular considering the role of forests and how persistent land conversion over a millennium has shaped the earth's surface and impacted climate stability. The set of "supporting ecosystem services" highlighted in the Millennium Ecosystem Assessment (MEA) coincides with the ground phase of the terrestrial water cycle, taking the concept beyond the ecosystem service perspective and identifying it as a planetary service. Ecosystem and planetary services differ in the same way that microeconomic and macroeconomic perspectives do. The water cycle intensity of a geographical area may well be related to a rainfall multiplier that measures the ability of continental ecosystems to increase the amount of water moving across terrestrial surfaces and descending as rainfall through transpiration and deposition, and re‐transpiration and re‐deposition of the water content in the air that originally arrives from the oceans. Building upon the MEA's association of human wellbeing with ecosystem features, the rainfall multiplier serves as a physical indicator and measure of the natural basis of wellbeing creation. This article is categorized under: Human Water > Water as Imagined and Represented Water and Life > Conservation, Management, and Awareness Human Water > Value of Water Abstract : The connection between the weakening intensity of the terrestrial water cycle and the notion of human well‐being as a declining asset.